حكم التبرك بالآثار النبوية الشريفة النعال النبوية أنموذجًا - Ahmed Mahmoud Ahmed Mahmoud Abu Hasouba; Muhammad Fakhruddin Bin Ishak; Abdul Halim Bin Abdul Karim (Fakulti Pengajian Quran dan Sunnah, 2024)
8TH International Prophetic Conference SWAN 2022 5th to 6th October 2022 (Hybrid Conference) Organized by: Faculty Of Quranic And Sunnah Studies